Safety culture as a contemporary healthcare construct: theoretical review, research assessment, and translation to human resource management - Palmieri, Patrick A. (2010)
Through a number of comprehensive reviews, the Institute of Medicine (IOM) has recommended that healthcare organizations develop safety cultures to align delivery system processes with the workforce requirements to improve patient outcomes. Until health systems can provide safer care environments, patients remain at risk for suboptimal care and adverse outcomes. Health science researchers have begun to explore how safety cultures might act as an essential system feature to improve organizational outcomes. Since safety cultures are established through modification in employee safety perspective and work behavior, human resource (HR) professionals need to contribute to this developing organizational domain. The IOM indicates individual employee behaviors cumulatively provide the primary antecedent for organizational safety and quality outcomes. Yet, many safety culture scholars indicate the concept is neither theoretically defined nor consistently applied and researched as the terms safety culture, safety climate, and safety attitude are interchangeably used to represent the same concept. As such, this paper examines the intersection of organizational culture and healthcare safety by analyzing the theoretical underpinnings of safety culture, exploring the constructs for measurement, and assessing the current state of safety culture research. Safety culture draws from the theoretical perspectives of sociology (represented by normal accident theory), organizational psychology (represented by high reliability theory), and human factors (represented by the aviation framework). By understanding not only the origins but also the empirical safety culture research and the associated intervention initiatives, healthcare professionals can design appropriate HR strategies to address the system characteristics that adversely affect patient outcomes. Increased emphasis on human resource management research is particularly important to the development of safety cultures. This paper contributes to the existing healthcare literature by providing the first comprehensive critical analysis of the theory, research, and practice that comprise contemporary safety culture science.